“Outside the Shul”: The American Soviet Jewry Movement and the Rise of Solidarity Orthodoxy, 1964–1986 - Ferziger, Adam S. (Religion and American culture, 2012)
Concern for the plight of Soviet Jewry grew steadily from the early 1950s. The rise of this issue to the forefront of American Jewish consciousness, however, was driven by the broader protest movement that emerged in the mid-1960s. Its central goal was to ensure civic and religious rights for Jewish residents of the Soviet Union, with a particular emphasis on the ability to emigrate. The movement's peak impact was in the 1970s. This decade witnessed the proliferation of grassroots organizations throughout the United States, along with the adoption of a more activist orientation by large segments of the American Jewish establishment. To date, minimal attention has been paid to the place of the Soviet Jewry movement in the religious history of American Judaism. The article's investigation of American Orthodoxy's role is intended to confront this lacuna and describes the central role played by Orthodox Jews in the rise and development of the Soviet Jewry movement. Through their actions, the members of this segment of American Jewry experienced a role reversal in which they helped to redefine the nature of the Jewish relationship to the public sphere. Simultaneously, such activism sharpened the internal divide between Modern Orthodoxy and its traditionalist counterparts who opposed demonstrations, encouraged quiet diplomacy, and were loathe to work in unison with the broader Jewish community. Through their involvement in a core Jewish activity that entailed partnership with non-Orthodox Jews in efforts for their common brethren, a generation of Modern Orthodox leaders arose that made Jewish solidarity a central expression of their Orthodox religious identities.